Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1126/sciadv.abq5751
|View full text |Cite
|
Sign up to set email alerts
|

Patterning the consecutive Pd 3 to Pd 1 on Pd 2 Ga surface via temperature-promoted reactive metal-support interaction

Abstract: Atom-by-atom control of a catalyst surface is a central yet challenging topic in heterogeneous catalysis, which enables precisely confined adsorption and oriented approach of reactant molecules. Here, exposed surfaces with either consecutive Pd trimers (Pd 3 ) or isolated Pd atoms (Pd 1 ) are architected for Pd 2 Ga intermetallic nanoparticles (NPs) using reactive metal-support interaction (RMSI). At elevated temperatures under hydrogen, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The composition of these compounds is highly dependent on gas atmospheres. [94,95] The weak interaction typically involves charge transfer between metal nanoparticles and support interface, termed electronic metal-support interaction (EMSI). [8,96] The magnitude and direction of charge transfer depend on Fermi level differences between the metal nanoparticle and the support, aiming for electron chemical potential equilibration.…”
Section: Types Of Metal-support Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of these compounds is highly dependent on gas atmospheres. [94,95] The weak interaction typically involves charge transfer between metal nanoparticles and support interface, termed electronic metal-support interaction (EMSI). [8,96] The magnitude and direction of charge transfer depend on Fermi level differences between the metal nanoparticle and the support, aiming for electron chemical potential equilibration.…”
Section: Types Of Metal-support Interactionsmentioning
confidence: 99%
“…Recent studies have suggested that adjusting the reduction temperature can fine-tune the composition of bimetallic alloys. Niu et al [95] subjected PdO/Ga 2 O 3 to different temperatures ranging from 100 °C to 600 °C in an H 2 /He atmosphere. They observed that PdO was reduced to different phases: Pd at 100 °C to 200 °C, Pd 2 Ga at 300 °C to 500 °C, and a combination of Pd 2 Ga and Pd 5 Ga 3 at 600 °C due to RMSI between Pd and Ga 2 O 3 .…”
Section: Effect Of Gas Environment On Reactive Metal-support Interactionmentioning
confidence: 99%
“…(22)(23)(24)(25) Among these techniques, in situ transmission electron microscopy (TEM) is a particularly powerful tool for studying the atomic structure and dynamic behavior of materials as it offers a real-time and real-space imaging of catalysts with high temporal and spatial resolution under external stimuli. (26)(27)(28)(29)(30)(31)(32)(33) In particular, the combined use of online mass spectrometry (MS) with in situ TEM has demonstrated a great potential in improving our understanding of the structure-performance relationships in catalytic processes, for instance, H 2 or CO oxidation. (34)(35)(36)(37) Yet, the majority of previous in situ / operando studies of Pd-based methane oxidation catalysis have used spectroscopic techniques with only a limited spatial resolution (e.g., X-ray absorption spectroscopy and X-ray photoemission spectroscopy).…”
Section: Introductionmentioning
confidence: 99%
“…23−27 We have also studied the interface mediated formation of PdZn and the refacetting of Pd 2 Ga NPs under a reducing atmosphere at elevated temperatures. 28,29 The combination of in situ TEM with spectroscopy techniques is therefore key to deepening the understanding of Pt redispersion on CeO 2 . Herein, we investigated the redispersion of Pt on CeO 2 , focusing on the impact of CeO 2 facets on redispersion at the atomic level.…”
mentioning
confidence: 99%
“…Atomic-scale control and mechanistic insights into redispersion highly rely on recognizing the dynamic structural evolution of Pt on CeO 2 under various chemical environments. The advent of in situ techniques has markedly advanced the observation of catalyst structure and behavior during reactions. , In situ transmission electron microscopy (TEM), in particular, is advantageous for monitoring the surface/interface dynamics of nanocatalyst at the atomic level. , This method has not only enabled direct observation of phenomena like Pt NP refacetting during CO oxidation but also revealed the critical role of support material properties and reaction environments in influencing the dynamic sintering and structural evolution of metallic NPs during catalytic processes. We have also studied the interface mediated formation of PdZn and the refacetting of Pd 2 Ga NPs under a reducing atmosphere at elevated temperatures. , The combination of in situ TEM with spectroscopy techniques is therefore key to deepening the understanding of Pt redispersion on CeO 2 .…”
mentioning
confidence: 99%